ViviSection: Skeleton‐based Volume Editing. (1st July 2013) - Karimov, A.; Mistelbauer, G.; Schmidt, J.; Mindek, P.; Schmidt, E.; Sharipov, T.; Bruckner, S.; Gröller, E.
Abstract: Volume segmentation is important in many applications, particularly in the medical domain. Most segmentation techniques, however, work fully automatically only in very restricted scenarios and cumbersome manual editing of the results is a common task. In this paper, we introduce a novel approach for the editing of segmentation results. Our method exploits structural features of the segmented object to enable intuitive and robust correction and verification. We demonstrate that our new approach can significantly increase the segmentation quality even in difficult cases such as in the presence of severe pathologies.